International Law 1960 to 2010: Now and Then - Keith, Kenneth J (Victoria University of Wellington Law Review, 2012)
In this tribute, I look back over 50 years of developments in selected areas of international law. I do this in part to prompt thought about future developments. I emphasise the importance of enduring principles and good process and the role they may play in facing massive new challenges arising across the globe, in balancing continuity and change, heritage and heresy.